2019
DOI: 10.1017/jan.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different phytases derived from E. coli AppA gene on the performance, bone mineralisation and nutrient digestibility of broiler chicken

Abstract: This study evaluated the effects of three different thermostable phytase variants, based on the AppA gene from E. coli (AppAT1, AppAT2 and AppAT3) on growth performance, nutrient digestibility and bone mineralisation in broiler chickens at inclusion levels of 250 and 500 FTU/kg. The eight treatment groups included a positive control (PC) which was sufficient in Ca and P, a negative control (NC, the same basal formulation as the PC, but reduced in Ca and P), and NC supplemented with AppAT1 at 250 and 500 FTU/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…In two of their experiments, they observed higher day-21 BW for birds fed diets with 1000 FTU of an uncoated phytase, compared to birds fed diets with the same inclusion of a coated phytase and a negative control with no phytase inclusion. Several studies have obtained similar results of increased body weight and feed intake with phytase supplementation at low and high inclusion levels [ 40 , 41 ]. This may be caused by the activity of phytase in the gastrointestinal tract, which contributes to the breakdown of IP 6 and lesser phytate esters, therefore increasing the availability of phytate-bound nutrients [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 72%
“…In two of their experiments, they observed higher day-21 BW for birds fed diets with 1000 FTU of an uncoated phytase, compared to birds fed diets with the same inclusion of a coated phytase and a negative control with no phytase inclusion. Several studies have obtained similar results of increased body weight and feed intake with phytase supplementation at low and high inclusion levels [ 40 , 41 ]. This may be caused by the activity of phytase in the gastrointestinal tract, which contributes to the breakdown of IP 6 and lesser phytate esters, therefore increasing the availability of phytate-bound nutrients [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 72%
“…The phytase enzyme that is the subject of this paper, Phytase TSP concentrate, to be marketed under the trade name OptiPhos® PLUS, is a novel thermostable 6-phytase developed for use as an ingredient in animal feed. Studies in weaned piglets and broiler chickens have demonstrated the high in vivo bioefficacy of the phytase [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%